Assertiveness as a Project Management Competency: A Systematic Review - Mc Donald, I.H.; Bond-Barnard, T.J. (The South African Journal of Industrial Engineering, 2025)
Assertiveness is increasingly recognised as a critical competency in project management, influencing communication styles, conflict management approaches, and interpersonal dynamics. However, it remains underexplored in the academic literature. This study addresses this gap by conducting a systematic literature review, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), to examine the role of assertiveness in project management environments. It also explores how assertiveness is experienced and perceived by both project managers and team members. The findings have implications for project management practice and education, highlighting the importance of assertiveness training and its strategic application. By bridging this research gap, the study enhances the understanding of how assertiveness contributes to project success.